Trend of self-reported asthma prevalence in Brazil from 2003 to 2013 in adults and factors associated with prevalence - Santos,Felipe Moraes dos (2018)
ABSTRACT Objectives: To determine the trend of self-reported asthma diagnosed prevalence and to describe the factors associated with asthma in Brazilian adults. Method: Epidemiological cross-sectional study based on databases analysis from three national household surveys: Pesquisa Nacional por Amostra de Domicílios (PNAD) 2003, PNAD 2008 and Pesquisa Nacional de Saúde (PNS) 2013. Participants between 18-45 years old were included. Trend analysis of asthma diagnosed prevalence was conducted using a logistic general linear model. A hierarchical logistic regression model was used to select factors significantly associated with asthma prevalence. Results: Asthma diagnosed prevalence was 3.6% (2003), 3.7% (2008) and 4.5% (2013), showing a statistically significant increased trend. Asthma diagnosed prevalence also increased when analysed by gender (annual change for men: 2.47%, p < 0.003; women: 2.16%, p < 0.001), urban area (annual change for urban: 2.15%, p < 0.001; rural: 2.69%, p = 0.072), healthcare insurance status (annual change without healthcare insurance: 2.18%, p < 0.001; with healthcare insurance: 1.84%, p = 0.014), and geographic regions (annual change North: 4.68%, p < 0.001; Northeast: 4.14%, p < 0.001; and Southeast: 1.84%, p = 0.025). Female gender, obesity, living in urban areas and depression were associated with asthma diagnosed prevalence. Discussion: PNAD and PNS surveys allow for a very large, representative community-based sample of the Brazilian adults to investigate the asthma prevalence. From 2003 to 2013, the prevalence of self-reported physician diagnosis of asthma increased, especially in the North and Northeast regions. Gender, region of residence, household location (urban/rural), obesity, and depression diagnosis seem to play significant roles in the epidemiology of asthma in Brazil.